Antibacterial Activity of a Fractionated Pistacia lentiscus Oil Against Pharyngeal and Ear Pathogens, Alone or in Combination With Antibiotics - Di Pierro, Francesco; Sagheddu, Valeria; Galletti, Serena; Forti, Mara; Elli, Marina; Bertuccioli, Alexander; Gaeta, Simone (Frontiers in Microbiology, 2021)
Previous studies have clearly demonstrated that the addition of lentisk oil (LO) to streptococcal cultures makes it possible to differentiate Streptococcus spp. into three categories with S. mitis and S. intermedius sensitive, S. pyogenes, S. agalactiae, and S. mutans partially sensitive, and S. salivarius insensitive to the product. We have investigated here whether the winterization of LO, an easy and cheap procedure that removes some of the fatty substances contained within, resulted in a better antimicrobial effect on human pathogens affecting the pharyngeal mucosa and middle ear such as S. pyogenes, S. pneumoniae, Moraxella catarrhalis, and Haemophilus influenzae, without affecting, or minimally affecting, S. salivarius strains, oral probiotics commonly used to reduce oral and middle ear infection recurrence, especially in children. Our results not only demonstrated a stronger antimicrobial action of winterized LO (WLO) on S. pyogenes, compared to what was seen with LO, but also demonstrated a strong antimicrobial action versus S. pneumoniae and M. catarrhalis and a very limited effect on S. salivarius (strains K12 and M18). Moreover, WLO demonstrated a synergistic action when tested along with the antibiotics amoxicillin and amoxicillin clavulanate, effects clearly visible also on H. influenzae. Our results also showed that at least part of the antimicrobial effect observed was due to the presence of anacardic acids (AAs). Finally, WLO, when tested with human peripheral blood mononuclear cells (h-PBMCs), reduced the release of IL-6 and TNF-α and, in the case of cells stimulated by LPS, of IFN-γ. In conclusion, our study highlights an enhanced antimicrobial role for LO when winterized, suggests a synergistic effect of this when given with antibiotics, identifies AAs as possible active ingredients, and proposes a possible anti-inflammatory role for it.